2016
DOI: 10.1016/j.jaap.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of transmethylation in anisole decomposition over HZSM-5: Experimental study

Abstract: This work investigated the decomposition of anisole (methoxyl-based lignin model compound) in a fluidized bed reactor over no catalysts and a series of HZSM-5 zeolite catalysts with different Si/Al atomic ratios. Transmethylation reaction was identified as the initial step of the thermal decomposition of anisole, leading to the prominent production of phenolic compounds. Methyl phenols were identified as the main products, with the yield of o-cresol being higher than that of p-cresol at the temperatures below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…However, it showed a BTX selectivity of 78.9 wt.%, lower than that obtained over Ni-Mo. Our research group has recently reported the conversion of anisole over non-metal HZSM-5 zeolite [10]. Compared to the results previously reported, both the yield and selectivity of BTX have been enhanced by the addition of the bimetallic sites (on average by 20% and 36% respectively) [10,32].…”
Section: Effect Of the Type Of Metal Combination On Deoxygenation Reamentioning
confidence: 70%
See 3 more Smart Citations
“…However, it showed a BTX selectivity of 78.9 wt.%, lower than that obtained over Ni-Mo. Our research group has recently reported the conversion of anisole over non-metal HZSM-5 zeolite [10]. Compared to the results previously reported, both the yield and selectivity of BTX have been enhanced by the addition of the bimetallic sites (on average by 20% and 36% respectively) [10,32].…”
Section: Effect Of the Type Of Metal Combination On Deoxygenation Reamentioning
confidence: 70%
“…Experiments were carried out in the bench scale fluidised bed reactor (Diameter*Height mm = 32mm×600mm); further details of the rig can be found in literature [10,32].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with a higher deactivation and lower cyclohexane selectivity observed for guaiacol HDO, the HDO of phenol/anisole mixture catalyzed with 0.8Rh‐HY‐R, even at low temperatures and high time space, exhibited high activity, stability, and selectivity toward deoxygenated products. These differences in deactivation rate and selectivity can be rationalized in two ways: 1) both the aromatic alcohol and the aromatic ether adsorb weakly to the catalyst surface and act as inefficient coke precursors; and 2) intermediate products derived from guaiacol transalkylation, such as catechol, methylcatechols, veratrole, and methylguaiacols, can also act as poisoning motifs for both the metallic and acid sites in the catalyst …”
Section: Resultsmentioning
confidence: 99%